OECD iLibrary.
De Organisatie voor Europese Samenwerking en Ontwikkeling publiceert jaarlijks zo’n 500 gratis e-books. Verder publiceren ze ook hele nuttige papers en statistieken over alle landen en over alle thema’s (bv. Onderwijs, economie, transport, wetenschap, voeding, …). // OECD iLibrary contains thousands of e-books, chapters, tables and graphs, papers, articles, summaries, indicators, databases and now also Podcasts - discoverable by theme, country or content type. Every year around 500 new titles are published via OECD iLibrary. Some of the themes are: Education, economy, transportation, science, nutrition...
Keywords: Multidisciplinair; Tijdschriftartikels